Ta’zir Keterlambatan Iuran Pemberi Kerja pada Dana Pensiun Syariah Perspektif Hukum Islam - Hidayati, Nova Rizky; Solihin, Solihin (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2024)
In Indonesia, the implementation of sharia pension funds is regulated in Law No. 4 of 2023 concerning Development and Strengthening of the Financial Sector, and POJK No.33 /POJK.05/2016 concerning the Implementation of Pension Programs Based on Sharia Principles. In determining a rule to be in accordance with sharia principles, the POJK should refer to Fatwa DSN Number: 88/DSN-MUI/XI/2013 concerning General Guidelines for Implementing Pension Programs Based on Sharia Principles. However, in the DSN-MUI fatwa there is no explanation of the ta'zir problem. This research is library research with a normative juridical approach, by examining legal sources related to ta'zir. The purpose of this research is to find out the law of ta'zir for late employer contributions contained in POJK No. 33 /POJK.05/2016 whether it is contrary to Islamic law or not. Based on several explanations contained in the Al-Quran, hadith, fiqh, DSN MUI fatwa on Employment Social Security, that the ta'zir sanctions listed in POJK No. 33 /POJK.05/2016 are not contrary to Islamic law. Where the aim is to achieve benefits in the management of pension funds so that pension benefits can be given properly to participants. However, in determining the amount of the fine, it should be limited in order to teach a lesson and not be excessive. The ta'zir funds that have been collected must be used as social funds, not included in the cash of the Islamic pension fund institution.